Polyethylenimine-based micro/nanoparticles as vaccine adjuvants - Shen C (Dove Medical Press, 2017)
Chen Shen,1 Jun Li,1 Yi Zhang,1 Yuce Li,2 Guanxin Shen,3 Jintao Zhu,2 Juan Tao1 1Department of Dermatology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China; 2School of Chemistry and Chemical Engineering, Huazhong University of Science and Technology, Wuhan, China; 3Department of Immunology, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China Abstract: Vaccines have shown great success in treating and preventing tumors and infections, while adjuvants are always demanded to ensure potent immune responses. Polyethylenimine (PEI), as one of the well-studied cationic polymers, has been used as a transfection reagent for decades. However, increasing evidence has shown that PEI-based particles are also capable of acting as adjuvants. In this paper, we briefly review the physicochemical properties and the broad applications of PEI in different fields, and elaborate on the intracellular processes of PEI-based vaccines. In addition, we sum up the proof of their in vivo and clinical applications. We also highlight some mechanisms proposed for the intrinsic immunoactivation function of PEI, followed by the challenges and future perspectives of the applications of PEI in the vaccines, as well as some strategies to elicit the desirable immune responses. Keywords: cationic polymers, APCs, immunoactivation, danger signals, anti-infection, anticancer